Application of roof-shape amines as chiral solvating agents for discrimination of optically active acids by NMR spectroscopy: study of match-mismatch effect and crystal structure of the diastereomeric salts - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (Journal of Organic Chemistry, 2016)
Optically active roof-shape amines were prepared and scanned as chiral solvating agents to study molecular recognition of acids by NMR analysis. Three types of amines were studied to establish a match mismatch effect for structurally diverse acid analytes. Single-crystal X-ray diffraction analysis was performed on the diastereomeric salts of roof shape amines and both isomers of mandelic acid to establish molecular conformation and correlate the absolute configuration with the observed NMR shift. The present system also recognizes the two isomers of weakly acidic BINOL and its derivatives.

Effect of substituent of roof shape amines on the molecular recognition of optically active acids by NMR spectroscopy - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (ChemistrySelect, 2020)
Optically active roof shape derivatives of benzyl amines were synthesized and screened as chiral solvating agents for the study of molecular recognition of chiral compounds by NMR and UV spectroscopy. The effect of substituents on the aromatic ring of benzyl unit is investigated to assess the binding ability with the analyte and an experimental correlation is observed. Altering the substituents on the ring of benzyl amine and the acidic substrates, significantly influence the CSA interactions. The supramolecular interactions between acid and amine in the single crystal X-ray analysis of the diastereomeric salts provide further insight of the mode of molecular recognition.
Keywords: Chiral Solvating Agents; molecular recognition; NMR spectroscopy; Roof Shape Amine; UV spectroscopy

Separation of isomers of chiral thiourea derivatives via spontaneous resolution and rationale of molecular recognition - Dwivedi, Astha M.; Gonnade, Rajesh G.; Sahoo, Suban K.; Bedekar, Ashutosh V. (CrystEngComm, 2025)
Enrichment of enantiomers during crystallization of racemic thiourea derivatives was investigated. The spontaneous resolution of a chiral thiourea derivative via preferential crystallization is attributed to thermodynamic stability when molecules of identical chirality bind with each other in the crystal lattice. Single crystal X-ray analysis reveals the interactions responsible for self-recognition of molecules of the same chirality in the unit cell. The tendency of the thiourea derivative to form a conglomerate is supported by IR spectroscopy, thermal analysis and computational studies.